A Retrospective Study on the Use of Chinese Patent Medicine in 24 Medical Institutions for COVID-19 in China - Zhang, Nan; Shi, Nannan; Li, Siyu; Liu, Guoxiu; Han, Yonglong; Liu, Li; Zhang, Xin; Kong, Xiangwen; Zhang, Bihua; Yuan, Wenpeng; Liu, Yi; Deng, Deqiang; et al. (Frontiers in Pharmacology, 2020)
Objective: This research aims to analyze the application regularity of Chinese patent medicine during the COVID-19 epidemic by collecting the names of the top three Chinese patent medicines used by 24 hospitals in 14 provinces of China in 4 time periods(20-22 January, 16-18 February, 1-3 March, 1-3 April 2020), and explore its contribution to combating the disease. Methods: ①We set up a database of the top three Chinese patent medicines used by 24 hospitals. ②The frequency and efficacy distribution of Chinese patent medicine were analyzed with risk area, region, and hospital of different properties as three factors. ③Finally, we analyzed the differences in the use of heat-clearing and non-heat-clearing medicines among the three factors(Chi-square test) and the correlation between the Chinese patent medicine and COVID-19 epidemic(correlation analysis) with SPSS 23.0 statistical software. Results: ① The heat-clearing medicine was the main use category nationwide during 20-22 January 2020. Meanwhile, there was a significant difference in the utilization rate of heat-clearing and non-heat-clearing medicine in different risk areas (P < 0.01). ② The variety of Chinese patent medicine was increased nationwide during 16-18 February 2020, mainly including tonics, blood-activating and resolving-stasis, and heat-clearing medicine. Meanwhile, there was a significant difference in the utilization rate of heat-clearing and non-heat-clearing medicine in the southern and northern regions (P < 0.05). ③ Tonics, and blood-activating and resolving-stasis medicine became the primary use categories nationwide during 01-03 March 2020. ④ The tonics class, and blood-activating and resolving-stasis medicine were still the primary categories nationwide during 01-03 April 2020. Meanwhile, there was a significant difference in the utilization rate of heat-clearing and non-heat-clearing medicine in different risk areas (P < 0.01). Conclusion: Chinese patent medicine has a certain degree of participation in fighting against the COVID-19. The efficacy distribution is related to the risk area, region, and hospital of different properties, among which the risk area is the main influencing factor. However, there are some problems in this study, such as uneven distribution in the region where 24 hospitals are located and limited time points, which need further in-depth discussion.